We have a segment CD, of which we know the midpoint M = (-1,-2) and one of the endpoints C = (4,3).
We have to find the coordinates of the other endpoint D.
We will use the fact that the coordinates x and y of the midpoint are the average of the coordinates x and y of the endpoints respectively.
Then, for the x-coordinates we can write:
![\begin{gathered} x_M=(x_C+x_D)/(2)_{} \\ 2\cdot x_M=x_C+x_D \\ x_D=2x_M-x_C \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mqrgx65i7hdol9nimdr3nuvaj2tn0f5k4m.png)
Then, we can calculate the x-coordinate of D from the x-coordinates of C and M.
The same can be written for the y-coordinates:
![y_D=2y_M-y_C](https://img.qammunity.org/2023/formulas/mathematics/college/1ssnxifk39ug7gqyzdb5tsk3yqfr56d6mv.png)
Then, we can replace and calculate each coordinate of D as:
![\begin{gathered} x_D=2x_M-x_C \\ x_D=2\cdot(-1)-4=-2-4=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w2nztq3r9blf815xtzqe8ngng827f16spz.png)
![\begin{gathered} y_D=2y_M-y_C \\ y_D=2(-2)-3=-4-3=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rzzeugae6ed2dmqbjgbv60vdamg5voh65k.png)
The coordinates of D are (-6,-7).
We can check with a graph as: